Evaluation of soft-tissue calcifications and their prevalence in the orofacial region using digital panoramic radiography: A retrospective study - Sharma , Shubha; Vinay Shinde , Christopher; Handa, Hina; Dawrani, Palak (Journal of Neonatal Surgery, 2025)
Soft-tissue calcifications of the orofacial region are commonly detected as incidental findings on panoramic radiographs. Although many are asymptomatic, certain calcifications may indicate underlying local pathology or systemic disease, highlighting the importance of their recognition during routine dental imaging. The present study aimed to assess the prevalence, anatomical distribution, and radiographic characteristics of soft-tissue calcifications in the orofacial region using digital panoramic radiographs and to evaluate their association with demographic variables. This retrospective, observational radiographic study was conducted at the Department of Oral Medicine and Radiology, People’s Dental Academy, Bhopal. A total of 800 digital panoramic radiographs of patients aged 18–60 years were evaluated for the presence of soft-tissue calcifications, which were classified according to type, anatomical location, laterality, number, and size using an eight-box classification system. Data were analyzed using SPSS version 30.0, applying descriptive statistics, Chi-square test, independent samples t-test, and one-way ANOVA, with statistical significance set at p < 0.05. Calcified stylohyoid ligament was the most prevalent finding (30.5%), followed by sialoliths (19.5%) and carotid artery calcifications (14%). Significant associations were observed between calcification characteristics and age, laterality, number, and size (p < 0.001), with unilateral and single calcifications predominating. Digital panoramic radiography is an effective screening modality for detecting a wide spectrum of orofacial soft-tissue calcifications, enabling early diagnosis and timely medical referral...